CONDITIONS AND QUALIFICATIONS OF A MEDIATOR-ARBITRATOR IN THE RESOLUTION OF FAMILY DISPUTES - Cusairi, Rafidah Mohamad; Zahraa, Mahdi (Journal of Islam and Science, 2015)
The Islamic law of tahkim (med-arb) has stipulated certain qualities which must be observed to qualify as a mediator- arbitrator. However, having understood that mediation is actually a method developed under the framework of tahkim and the person who conducts it is by right an arbitrator, it poses the question of whether a mediator-arbitrator is required to possess qualifications similar to those of arbitrator. This paper seeks to examine and analyse the conditions and qualifications of a mediator and an arbitrator from the Islamic law perspective. The study adopts content analysis approach. It is therefore conducted based on and with reference to the Islamic law method of med-arb (tahkim) as discussed by Muslim jurists in classical texts. The findings show that in Islamic law of tahkim, a mediator and an arbitrator share almost similar roles in resolving marital disputes. A mediator and an arbitrator supposedly reflect each other in character and qualifications in many ways if not all.